If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2k + 1)(2m + 1) = 0 Reorder the terms: (1 + 2k)(2m + 1) = 0 Reorder the terms: (1 + 2k)(1 + 2m) = 0 Multiply (1 + 2k) * (1 + 2m) (1(1 + 2m) + 2k * (1 + 2m)) = 0 ((1 * 1 + 2m * 1) + 2k * (1 + 2m)) = 0 ((1 + 2m) + 2k * (1 + 2m)) = 0 (1 + 2m + (1 * 2k + 2m * 2k)) = 0 (1 + 2m + (2k + 4km)) = 0 Reorder the terms: (1 + 2k + 4km + 2m) = 0 (1 + 2k + 4km + 2m) = 0 Solving 1 + 2k + 4km + 2m = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 2k + 4km + -1 + 2m = 0 + -1 Reorder the terms: 1 + -1 + 2k + 4km + 2m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2k + 4km + 2m = 0 + -1 2k + 4km + 2m = 0 + -1 Combine like terms: 0 + -1 = -1 2k + 4km + 2m = -1 Add '-2m' to each side of the equation. 2k + 4km + 2m + -2m = -1 + -2m Combine like terms: 2m + -2m = 0 2k + 4km + 0 = -1 + -2m 2k + 4km = -1 + -2m Reorder the terms: 1 + 2k + 4km + 2m = -1 + -2m + 1 + 2m Reorder the terms: 1 + 2k + 4km + 2m = -1 + 1 + -2m + 2m Combine like terms: -1 + 1 = 0 1 + 2k + 4km + 2m = 0 + -2m + 2m 1 + 2k + 4km + 2m = -2m + 2m Combine like terms: -2m + 2m = 0 1 + 2k + 4km + 2m = 0 The solution to this equation could not be determined.
| -2-ln(x+1)=0 | | 20x^2-2x-4=0 | | 72x^2+96x-936=0 | | 4x+-6=34 | | -2x-(-8+3x)=6 | | y=-3x+-8 | | 3x+12-7*3x=123 | | (y+7)(y-8)= | | 72x^2-2496x-936=0 | | 98-7(10)= | | 98-7(-5)= | | (8x+1)-(-5x+5)= | | 98-7(280)= | | 2x^2-18x+45=0 | | y=5E-06x+0.24 | | 11=18-x | | (7x+5)+(-8x+6)= | | 0.29=logx | | x=log(3)(48) | | 3/4t-6=1/3t-1 | | 3/2t-6=1/3t-1 | | nx+b=6(x-n)forx | | nx+b=6(x-n) | | 3x(x+4)=3(x-1) | | 70-1.5(4)= | | 6y-15=3y+6 | | 144s^2-225c^2=0 | | s^2-2s+16=0 | | (a+b)c=(b+a)c | | 70-1.5(2)= | | 9x+-5(3x+-12)=30 | | -(5)+y=4 |